"No One Really Likes Crying in School": The Influences of Classroom and Institutional Dynamics Upon Student Absenteeism During COVID-19. Issue 1 (25th August 2022) - Kipp, Andrew Louis
The COVID-19 pandemic has worsened the already problematic issue of student absenteeism. This study uniquely employs an ecological agency approach to better understand student absenteeism during COVID-19. Using a case study methodology, the study captures the experiences of two absentee students within a United States suburban high school during the 2020–2021 school year to better understand the institutional structures motivating their daily decision to attend or miss school. In the remote learning environment, rigorous curricular expectations, minimal social interactions, teacher-led instruction as a response to student disengagement from student-led instruction, and lower teacher expectations contributed to the participants' daily decision to miss school. In the remote, hybrid, and full-time in-person learning spaces, staff apathy toward bullying, minimal space to escape feelings of anxiety, and fewer tutoring outlets motivated student absenteeism. Therefore, the school environment can better promote attendance during COVID-19 by establishing an in-school space to escape heightened anxiety, academic supports to reduce grade-induced anxiety, shifting from nonintervention to prosocial instructional interventions in all learning environments, teacher voices in policy design, reducing teacher-led instruction, and shifting teacher beliefs to an asset mindset. Recommendations for future research are included.